2002
DOI: 10.1074/jbc.m107710200
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of theSchizosaccharomyces pombe Origin Recognition Complex

Abstract: The origin recognition complex (ORC) plays a central role in the initiation of DNA replication in eukaryotic cells. It interacts with origins of DNA replication in chromosomal DNA and recruits additional replication proteins to form functional initiation complexes. These processes have not been well characterized at the biochemical level except in the case of Saccharomyces cerevisiae ORC. We report here the expression, purification, and initial characterization of Schizosaccharomyces pombe ORC (SpORC) containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
61
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 42 publications
7
61
0
Order By: Relevance
“…Thus, the overall affinity of SpOrc4 for such a sequence would be a complex function of the number of possible binding modes and the binding affinity of each mode and would be expected to increase with AT content and length. Consistent with these ideas, it has been demonstrated experimentally that SpOrc4 has significant affinity for multiple sites within a single ars element (41)(42)(43)46). Moreover, genetic studies have shown that sequences capable of functioning as origins contain multiple redundant AT-rich elements that contribute to activity (14-16, 18, 38).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Thus, the overall affinity of SpOrc4 for such a sequence would be a complex function of the number of possible binding modes and the binding affinity of each mode and would be expected to increase with AT content and length. Consistent with these ideas, it has been demonstrated experimentally that SpOrc4 has significant affinity for multiple sites within a single ars element (41)(42)(43)46). Moreover, genetic studies have shown that sequences capable of functioning as origins contain multiple redundant AT-rich elements that contribute to activity (14-16, 18, 38).…”
Section: Discussionmentioning
confidence: 55%
“…Biochemical studies have shown that the S. pombe origin recognition complex is targeted to origins by the N-terminal domain of SpOrc4, which contains nine AT-hook motifs (40)(41)(42)(43). The AT-hook motif binds to short AT tracts of 4-6 nt in length in the minor groove of DNA (44).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the spOrc4p alone binds to DNA as efficiently as spORC. The importance of the N-terminal AT hook domain was further substantiated by the finding that this region of spOrc4p is essential for viability in vivo (8).…”
mentioning
confidence: 75%
“…The structure and initiator role of ORC is conserved in all eukaryotes, and six-subunit complexes have been purified from species including Schizosaccharomyces pombe (sp), Drosophila melanogaster (Dm), Xenopus laevis, and humans (7)(8)(9)(10)(11). In vitro and in vivo studies indicate that although ORC is essential for DNA replication in these species (1), the sequences recognized by these ORC complexes differ.…”
mentioning
confidence: 99%
“…They could include (dT) n (dA) n sequences predominantly distributed in a mirror repeat manner, and as reported, involved in initiator protein binding (5,(12)(13)(14)(15)(16)(17)(18). The structural impact of these sequences was not investigated, but numerous other studies confirm that A and T tracts (depending on their distribution and size) could profoundly affect geometry of grooves, bending, and the ability to bend or formation of loops and multistranded structures (19).…”
mentioning
confidence: 99%